The California casa - Wood, Douglas; Levick, Melba.;Tichenor, Brian (New York : Rizzoli International Publications, Inc., 2012)
The Spanish style in architecture encompasses facets from a vast array of traditions, many of which are in evidence in these extraordinary houses. Elements include thickset, whitewashed stucco walls, deeply recessed doors, lushly planted courtyard gardens, intricate and colorful tile work, telescoping towers inset with Juliet balconies, elaborately traced wrought-iron window grilles, and richly appointed interiors heightened by drama in light and shadow cast by moody pendant lamps and low-burning fires. The houses featured are the very best of the type, both famous and little-known, and showcase the work of architects such as George Washington Smith, Bertram Goodhue, Wallace Neff, and Paul Williams, from the early twentieth century, to the work of contemporary practitioners, including Marc Appleton, Michael Burch Architects, and others. These homes are a fantasy for living made real in the Southern California sun.
Preface -- Introduction by M. Brian Tichenor -- Coppell mansion -- A.I. root house -- Christianancy estate -- Prindle house -- Steedman estate -- Wilson house -- Sherwood house -- Ford house -- Gould house -- Collins house -- Barker house -- Longan estate -- Burnham house -- Chimorro house -- Sills-Kenyon house -- McNeil House -- Hanson house -- Hacienda Mojica -- Long house -- Rosson house -- Wanberg house -- Steinbeck house -- Cotton estate -- Kelly house -- Earl estate -- Gosser house -- Mead house -- Overell estate -- Villa Primavera and the Andalusia -- The rindge/Adamson legacy -- Adamson house -- Morgan house -- Keeler house -- Collector's home -- Casa Salchicha -- Acknowledgments -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: ARCHITECTURE, DOMESTIC -- CALIFORNIA, SOUTHERN -- SPANISH INFLUENCES -- PICTORIAL WORKS